The unmanned vehicle - Lukman, Najah; Abdul Wahid, Khalid; Hamdan, Haslenna; Ab Razak, Wan Maziah (Fakulti Pengurusan Perniagaan, UiTM Terengganu, 2023)
November 2016 had witnessed the world first delivery of pizza by Domino's Pizza. A New Zealand couple has become the first people in the world to have a pizza delivered by drone to their home in Whangaparaoa, about 20 miles north of Auckland (Reid, 2016). The discussion by Trott (2017) on drone however had focused on the issues raised on unmanned drone, which are safety, privacy, and cost.